Evolution of cephalic structures in extreme myrmecophiles: a lesson from Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae). (26th January 2022) - Jałoszyński, Paweł; Luo, Xiao‐Zhu; Beutel, Rolf Georg
Abstract: Pselaphinae is a large subfamily, comprising over 10 000 species of the megadiverse Staphylinidae (rove beetles). A remarkable feature of this group is the extreme structural diversity of different body regions, especially the head and its appendages. Within Pselaphinae, Clavigeritae stand out as a clade of highly specialized myrmecophiles. We examined internal and external head structures of the clavigerite species Diartiger kubotai Nomura, using state‐of‐the‐art techniques. The cephalic morphology indicates in a phylogenetic context that the loss of eyes in some Clavigeritae was the latest of major evolutionary changes. We compiled the largest set of morphological data ever scored for the subfamily, comprising 155 characters of the head. Parsimony analyses and Bayesian inference yielded a similar phylogenetic pattern, largely congruent with results published previously. We retrieved Pselaphinae as a clade, and Faronitae as sister to all remaining groups of the subfamily. Faronitae are followed by a "Euplectitae grade" and non‐monophyletic Goniaceritae, Batrisitae and Pselaphitae. Clavigeritae are monophyletic, but have evolved within the pselaphite grade. The enigmatic Colilodion Besuchet, recently shifted from Clavigeritae to a paraphyletic Pselaphitae, was placed as sister to extant clavigerites based on an array of cephalic synapomorphies. The current classification of Pselaphinae is unstable and deep changes should be made maintaining only monophyletic units, whereas most of the supertribes are paraphyletic. Characters of the head, with a concentration of mouthparts and sensory structures, and essential parts of the digestive tract and the nervous system, are highly informative phylogenetically. Study of internal structures, presently still at a very preliminary stage, obviously is essential for understanding the evolution of Pselaphinae. Future genetic investigations may reveal mechanisms behind the unique structural megadiversity in this exceptional group of rove beetles.